Survey of Crowd Detection Algorithms using Wireless Sensor Networks - Obbo, Aggrey; Nabaasa, Evarist (International Journal of Computer Applications, 2019)
In this paper a survey is carried out on crowd detection algorithms, highlighting challenges and gaps vis-a-avis people crowd detection. The research identifies some of the key capabilities considered invaluable in effective people crowd detection and compares some of the current crowd detection algorithms with regard to these. The results reveal that most algorithms are primarily non-people crowd detection algorithms. While people crowds are intelligent and can easily bypass most of the current crowd detection algorithms. Given the need for detection and management of people crowds, there is great need for specialized algorithms for people crowd detection using effective and non resource intensive methods .
A Case of People Crowds
Keywords: Crowd Detection Algorithms; People Crowds Detection